Strategi Mempertahankan Keunggulan Kompetitif PT Jayamandiri Gemasejati - Sukabumi - Mansur, Umar; Zulfikri, Agung (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2020)
Jayamandiri Gemasejati is a company engaged in the Yamaha Motor and Spare Parts Sales Industry. This study aims to describe how the method used in this study is a descriptive method using a descriptive approach. Analysis of research data was carried out by identifying various internal and external factors through PT Jayamandiri Gemasejati's IFE, EFE, and SWOT matrix analysis. The identification and mapping of the key factors of the IFE and EFE matrices indicate that PT Jayamandiri Gemasejati is in a strong position and can well take advantage of opportunities and deal with existing threats with the strength they have, where Total IFE shows 2.69 and Total EFE shows 3,22 which indicates a strong internal and external position.